Kazakhstan Tourism Industry in Promoting Sustainable Agriculture Development - AINAKANOVA, Bakytgul; NUKESHEVA, Anar; SUNDETULY, Zhaskairat; KAZKENOVA, Aigul; OMARKHANOVA, Zhibek; YERNAZAROVA, Anar (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023DO - 10.14505/jemt.v14.2(66).24, 2023)
The expansion of such an area of tourism industry as agrotourism is a breakthrough for the development of rural industry. In addition, the integration of agro-tourism with agricultural eco-efficiency is closely related to agro-ecological development, therefore, it is necessary to study the relationship between the two in order to realize quality agro-ecological development. Integration of agriculture with other industries is an important means of expanding the agro-industrial chain and is useful for promoting sustainable agricultural development. The purpose of this study is to analyze the improvement of competitiveness of agricultural enterprises in the Republic of Kazakhstan through diversification of production and its impact on the tourism industry, including tourism enterprises. The degree of effectiveness of implementation of management decisions aimed at the development of tourism and agribusiness depends on the level of development of infrastructure and services in a particular region of the country. In this context, statistical data on the development of tourism and its relationship with agribusiness in the Republic of Kazakhstan are used to analyze some factors affecting their development.